Classroom management practices of English Language Teachers: A Study of senior high schools in Agona West Municipality - Daniel Arkoh Fenyi; Emmanuel Owusu (goodwood publishing, 2022)
Purpose: This study aimed to ascertain (1) the classroom management practices of language teachers (2) the challenges in implementing the management practices and (3) the importance of classroom management to language pedagogy. Research methodology: The study is qualitative. It used observation and semi-structured interview to engage 22 language teachers selected through random sampling from all the four Senior High Schools in the Agona West Municipality... 3 language class sessions were observed... The data were analyzed thematically Results: It was found that teachers were aware of the relevance of classroom management in language teaching. They employed good student-teacher relationships, deference, physical organization of the classroom, and professionalism in managing the class in spite of challenges such as insufficient and ineffective teaching/learning resources, indiscipline, and large class size among others in the classroom. Limitations: The use of only one approach- - makes it difficult to generalize the findings. Contribution: The study extends knowledge on classroom management in the second language context, and further provides evidence and empirical data for teachers and policymakers to understand the relationship between students’ academic achievement and classroom management.